World View in Indonesian Novels - Dwi Desi Fajarsari; Teguh Supriyanto; Agus Nuryatin; Ida Zulaeha (Universitas Negeri Semarang, 2022)
Abstrak. Literary works have total meaning if it is realized that the literary work contains the author's world view that represents himself as well as his collective subject. The purpose of this research is to find the world view in the novels SBDBS, LTLA, and NDTR. This literary research uses a sociological approach to literature, especially genetic structuralism. In accordance with literary research with the theory of genetic structuralism, the research methodology used is the Goldmann dialectical method. The results of the study show tha t the SPDBS novel has a narrative structure built on a plot with the theme of unitary nationalism, LTLA raises the story of the inner conflict of members of the rebel army, and NDTR about patriotism. The world view found in the SPDBS novel is nationalism to fight against rebel groups and create a peaceful life, while LTLA has the view that the inner struggles of rebel characters are considered so that all can feel justice, and NDTR has a patriotic world view through the heroic character of Hasan Saleh who can fight for provincial autonomy. Aceh. This world view is related to the collective subject of the author as the creator. The influential social structure is economic class and education level.